ILLOCUTIONARY ACT IN THE MAIN CHARACTERS’ UTTERANCES IN MIRROR MIRROR MOVIE - Rahayu, Fita Nur; Arifin, M. Bahri; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2018)
ABSTRACT The aims of this research were to find out the types of illocutionary act of the main characters’ utterances in Mirror Mirror movie by Searle’s theory of illocutionary act and to find the context underlying illocutionary act of the main characters by Hymes’ SPEAKING model in Mirror Mirror movie. This research was descriptive qualitative because the data were the utterances of the characters in the Mirror Mirror movie. There were some steps in collecting the data: downloading the movie script, watching the movie several times, reading and observing the dialogue in the movie and selecting Queen and Snow White’s utterances that contain illocutionary act. In the data analysis, the researcher applied Miles and Huberman’s procedures namely data reduction, data display and conclusion drawing/verification. The results of the research show that there are 55 utterances of the main characters that contain illocutionary act. The data were classified into five namely are representatives (4), directives (37), declaratives (0), commissives (2), expressives (12). Of the total 55 illocutionary acts, directives are the most frequent types of illocutionary act because the main characters mostly expressed their utterances in direct way such as by ordering, requesting, asking and commanding. Conversely, the declarative types of illocutionary act were not appeared in this research because the characters that performed the utterance that contain illocutionary act were not selected as the object to analyze. There were eight factors affecting the illocutionary act of the main characters using the context of Hymes’ SPEAKING model. They are setting, participants, ends, act, sequences, key, instrumentalities and genre. Keywords: Speech Act, Illocutionary Act, SPEAKING model by Hymes,Mirror Mirror Movie  ABSTRAK  Tujuan dari penelitian ini adalah untuk mencari jenis-jenis tindak ilokusi pada tuturan tokoh-tokoh utama dalam film Mirror-Mirror menggunakan teori dari Searle dan untuk menemukan konteks pada tindak ilokusi tokoh-tokoh utama menggunakan SPEAKING model dari Hymes. Penelitian ini merupakan deskriptif kualitatif karena data berupa tuturan tokoh-tokoh di film Mirror Mirror. Ada beberapa langkah dalam mengumpulkan data: mengunggah naskah film, menonton film beberapa kali, membaca dan meneliti percakapan didalam film dan memilih tuturan Snow White dan Queen yang mengandung tindak ilokusi. Didalam data analysis, peneliti menerapkan prosedur Miles dan Huberman yaitu reduksi data, penyajian data, verifikasi/ penarikan kesimpulan. Hasil penelitian menunjukkan bahwa ada 55 tuturan tokoh-tokoh utama yang mengandung tindak ilokusi. Data diklasifikasikan menjadi lima yaitu representatives (4), directives (37), declaratives (0), commissives (2), expressives (12). Dari total 55 tindak ilokusi, directives adalah jenis tindak ilokusi yang paling sering muncul karena tokoh-tokoh utama sebagian besar mengekspresikan tuturan mereka secara langsung seperti memesan, meminta, bertanya dan menyuruh. Sebaliknya, tindak ilokusi declaratives tidak muncul dalam penelitian ini karena tokoh-tokoh yang melakukan tuturan yang mengandung tindak ilokusi tidak dipilih sebagai objek untuk dianalysis. Ada delapan faktor yang mempengaruhi tindak ilokusi menggunakan teori konteks SPEAKING dari Hymes. Mereka adalah setting, participants, ends, act, sequences, key, instrumentalities and genre. Kata Kunci: Tindak Tutur, Tindak Ilokusi, SPEAKING model oleh Hymes, Film Mirror Mirror